TANGGUNG JAWAB PENGUSAHA KAPAL ATAS PEMBERIAN JAMINAN SOSIAL TENAGA KERJA (JAMSOSTEK) TERHADAP AWAK KAPAL - OLIVIA, FITRIA; SUTANTO, JEFFREY (Proceeding SENDI_U, 2015)
In the maritime sector, some three decades that the maritime sector is a sector position of the periphery,because economic growth is so slow that make this sector becomes less government attention. It is time forour nation to change the perspective of development of land-based development only became more orientedto the marine base in view of our country is an island nation that has been recognized and accommodated inthe 1945 Constitution, Article 25A. Therefore everyone working at sea should also be protected so that theneed for marine work agreement between the employees and ship owner. Based on background research,there are two problems as major issues in marine sector that required serious attention from our government,particularly from Ministry of Marine Affairs and Fisheries Republic of Indonesia, are: First, how dorelationship in seafarerâs employment agreement between employees and ship owner? And then Second, isthe seafarerâs employment agreement already protect the rights and social guarantee of employees yet? Thisresearch methods will be used in this paper is descriptive research of literature method.The relationshipbetween the labor agreement with the employer ship crew is doing treaty rights and obligations and workagreements have been protected by Act 3 of 1992 and PP 14, 1993.Keywords: Responsibility, Entrepreneur Boats, Social Security Labor, Crew